Effect of temperature and salinity on the seagrass Halophila baillonii (Hydrocharitaceae) under aquarium conditions - Olvido van Barneveld Pérez, Carla; Samper-Villarreal, Jimena (Revista de Biología Tropical, 2025)
Introduction: Halophila baillonii, also known as “clover grass”, is a rare seagrass species found in tropical waters off the American continent. This is a small and ephemeral species classified as Vulnerable in the IUCN Red List. Objective: To determine how variations in temperature and salinity affect this seagrass. Methods: H. baillonii was collected in the southern Pacific coast of Costa Rica either by hand or with a corer (8 cm diameter). Two experiments with three treatments each were carried out in aquaria. Each treatment was applied to three aquaria, for a total of nine aquaria per experiment. The temperature treatments consisted of 23 °C (Low), 28 °C (Control), 33 °C (High), with a constant salinity of 25 over 51 days. Salinity treatments were 15 (Low), 25 (Control), 35 (High) with a constant minimum temperature of 28 °C over 31 days. Five plant performance parameters were measured: 1) foliar shoot survival; 2) increase in the number of foliar shoots; 3) horizontal rhizome elongation; 4) rhizome internodal length; and 5) leaf area. Results: H. baillonii survival rates were higher when collected manually rather than using a corer. All plant performance parameters were higher at 28 °C temperature (control). In contrast, variables of plant performance were similar in all salinity treatments, except that the seagrass presented smaller leaves at higher salinities. Female flowers were found towards the end of the experiments, being the first report of flowering of this species under aquaria conditions. Conclusion: H. baillonii has a wide salinity tolerance, thus enabling plant survival during dry or rainy seasons. In contrast, H. baillonii appears to be more sensitive to lower and higher temperatures than 28 ºC. This is the first study reporting the response of this threatened species to experimentally induced fluctuations of temperature and salinity.